2015
DOI: 10.1093/occmed/kqu200
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of UK Armed Forces medical personnel post-deployment

Abstract: These results suggest that while the overall rates of self-reported mental health disorders were similar in FMs and RLMs, FMs reported more PTSD symptoms than all other roles, which may have been related to working in more hostile environments in more challenging roles while deployed and their experiences on returning home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Protection of mental health for healthcare professionals at frontline of pandemic situation is critical, not only for successful termination of COVID-19 pandemic in the long term [ 62 ] but also for prevention of suffer of PHDs and military medical staffs from post-traumatic stress symptoms after deployment [ 63 , 64 ]. Also, the current study revealed possible protective factors of mental health for PHDs with working experiences at frontline of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of mental health for healthcare professionals at frontline of pandemic situation is critical, not only for successful termination of COVID-19 pandemic in the long term [ 62 ] but also for prevention of suffer of PHDs and military medical staffs from post-traumatic stress symptoms after deployment [ 63 , 64 ]. Also, the current study revealed possible protective factors of mental health for PHDs with working experiences at frontline of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In men, the development of a CMD is more often driven by whether they felt capable of undertaking the task asked of them in relation to their trade or experience. For women, the development of a CMD depends on whether there was a perception that their life was threatened, or they may be injured 35 . There is some evidence to suggest that shooting at or killing an enemy may be more traumatic than coming under fire 36 .…”
Section: Deployment and Combatmentioning
confidence: 99%
“…Research shows that UK military personnel who have deployed in combat roles are a high-risk group for developing PTSD 26 27. Despite this, the incidence of PTSD remains relatively low 2.…”
Section: Why Is Resilience Important To the Military?mentioning
confidence: 99%
“…In the UK military, both decompression and TRiM have proved beneficial for military personnel returning from deployments or who have been involved with a traumatic event 41. TRiM has been shown to enhance line manager support and reduce sickness absence 26. The Stress and Resilience Centre at Shrivenham runs the ‘Leading by Example’ courses, which aim to equip personnel with strategies to help them deal with life stress 42.…”
Section: Current Resilience Building Strategiesmentioning
confidence: 99%